Scientific information asset management: A perspective for research and education in Europe? - Mester, J.; Wigger, U. (International Journal of Computer Science in Sport, 2003)
For many years universities have been the most prominent institutions for science, research and education. One of the most important objectives is the creation of Information assets. In the current situation of decreasing public funding and increasing competition from private research institutions and high-calibre corporate universities, the leading position of public universities is being threatened. The first step to remedy this situation is to analyse possible weaknesses and reconsider potential strengths in the frame of modern information technologies. Computer science is taking on a crucial role as the development of HMS (hard-, middle-, Software) is becoming extremely complex with continuously rising demands for the maintenance of such systems. The technical concept of an Information Asset Management needs to take into account the infrastructure of classical universities with wide-spread competencies and non-hierarchical organisations as well as legal rules and implications set by the European Union.